Analysis of Sales Growth and Financial Factor Determining Dividend Distribution Policy: A Sample of Indonesia Manufacturing Companies - Hadi Ismanto; Amanatur Rohmah Rofi’ Indayanti (Jurnal Manajemen Indonesia, 2021)
A company's dividend policy will involve two parties, between the investor and the company. The parties have different interests. Companies that have an interest in holding profits and the interests of investors who want the distribution of dividends. Investors usually prefer to pay a very high price for stocks that can provide high dividends. This study combines the factors that influence the distribution of dividends in one study frame. The research objective is to test and analyze the factors that influence the distribution of dividends in a manufacturing company for the period of 2016-2017 listed on the Indonesia Stock Exchange by using variables of sales growth, asset turnover (TATO), NPM, ROI, CR, DER. The method used in this research is descriptive with a total sample of 133 companies with a purposive sampling technique. Analysis of the data used is logistic regression analysis. The results showed that only the TATO variable and the ROI variable influenced the distribution of dividends. While the variable Sales growth, NPM, CR, DER do not affect the distribution of dividends. For companies, financial health is the main thing by always paying attention to financial ratios and dividend policy strategies. Investors are expected to understand and pay attention to asset turnover and return on investment, so the decision made is the right choice. Keywords— Dividend policy; dividend distribution policy; financial ratio; sales growth